2018
DOI: 10.1080/2162402x.2017.1412902
|View full text |Cite
|
Sign up to set email alerts
|

TNFa and IL-2 armed adenoviruses enable complete responses by anti-PD-1 checkpoint blockade

Abstract: Releasing the patient's immune system against their own malignancy by the use of checkpoint inhibitors is delivering promising results. However, only a subset of patients currently benefit from them. One major limitation of these therapies relates to the inability of T cells to detect or penetrate into the tumor resulting in unresponsiveness to checkpoint inhibition. Virotherapy is an attractive tool for enabling checkpoint inhibitors as viruses are naturally recognized by innate defense elements which draws t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 55 publications
(76 reference statements)
3
100
0
Order By: Relevance
“…We also observed that when used with oAD-IL7, the tumor in ltrating T cells presented elevated PD1 and LAG-3 expression. This result has also been observed in previous study, such as using IL12 loaded oncolytic vaccinia, IL2 loaded oncolytic adenovirus, or bispeci c antibody loaded oncolytic adenovirus [27][28][29]. Other than T cells exhaustion, this result has been widely reported and was regarded as a sign of increased activation of tumorin ltrating T cells.…”
Section: Discussionsupporting
confidence: 85%
“…We also observed that when used with oAD-IL7, the tumor in ltrating T cells presented elevated PD1 and LAG-3 expression. This result has also been observed in previous study, such as using IL12 loaded oncolytic vaccinia, IL2 loaded oncolytic adenovirus, or bispeci c antibody loaded oncolytic adenovirus [27][28][29]. Other than T cells exhaustion, this result has been widely reported and was regarded as a sign of increased activation of tumorin ltrating T cells.…”
Section: Discussionsupporting
confidence: 85%
“…17,30 In contrast, other studies suggest that viral therapy can be enhanced by blockage of the PD-1:PD-L1 interaction and the combined therapy can increase antitumor efficacy. 42 In summary, synergistic antitumor effects were observed in the humanized mice treated with the combination of ONCOS-102 and pembrolizumab as demonstrated by reduced tumor volumes. Our results lead us to hypothesize that ONCOS-102 induced cell death of the tumor cells by recruiting immune cells to the tumor environment.…”
Section: Daymentioning
confidence: 88%
“…Arming oncolytic adenoviruses (OAds) with therapeutic transgenes is an attractive approach to increase their efficacy. OAds are a highly versatile therapeutic platform that allow oncoselective expression of a wide range of therapeutic molecules such as cytokines 9 , extracellular matrix modulators 7,10 , immune checkpoint blockades (IBCs) 11 , bi-specific T-cell engagers (BiTEs) 12 or prodrug converting enzymes 13 , allowing a multimodal tumour attack, from direct cell lysis to tumour microenvironment modulation.…”
Section: Introductionmentioning
confidence: 99%